Pengaruh Aromatheraphy Lemon Terhadap Mual Muntah Ibu Hamil Trimester I Di Puskesmas 7 Ulu Kota Palembang - Dita Rahmalia Putri; Ranida Arsi; Fitri Afdhal; Alkhusari Alkhusari (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Introduction: Pregnancy is a process of physiological changes such as nausea, vomiting, dizziness, back pain, black spots on the face, leg cramps, weight gain, insomnia, and frequent urination. The cause of nausea and vomiting is due to an increase in the hormone estrogen and Human Chorionic Gonadrotropin (HCG). Nausea and vomiting can be prevented by pharmacological and non-pharmacological methods. Non-pharmacological treatment for nausea and vomiting is lemon aromatherapy. Objectives: This study aims to determine the effect of giving lemon aromatherapy on reducing nausea and vomiting in first trimester pregnant women at the 7 Ulu Community Health Center, Palembang City in 2024. Methods: This research uses a quasi-experiment using a research design (pretest-posttest with control group). This research was divided into 2 groups, namely the intervention group and the control group. The sample in this study consisted of 28 respondents who were divided into 2 groups, the sampling technique was purposive sampling. Data analysis technique using the Wilcoxon test. Results: The results of the research after carrying out a significant test using the Wilcoxon test showed that there was a significant influence or change with a p-value of 0.001, which means <0.05. Conclusions: From the results of this research, it is hoped that pregnant women in the first trimester can apply lemon aromatherapy as an alternative non-pharmacological therapy to treat nausea and vomiting in pregnant women in the first trimester.